2020
DOI: 10.1002/jor.24800
|View full text |Cite
|
Sign up to set email alerts
|

Formation process of joint contracture after anterior cruciate ligament reconstruction in rats

Abstract: Knee joint contracture is often induced by anterior cruciate ligament reconstruction (ACLR). However, the temporal and spatial arthrofibrotic changes following inflammatory events, which occur in parallel with the formation of joint contractures after ACLR, are unknown. This study aimed to reveal: (a) time-dependent changes in myogenic and arthrogenic contractures; and (b) the process of arthrofibrosis development after ACLR. ACLR was performed on knees of rats unilaterally. Passive ranges of motions (ROMs) be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This indicates that intermuscular collagen deposition began to increase in the rst week of immobilization, but decreased after 4 weeks of immobilization. Previous studies have shown that this may be associated with gradual resolution of the in ammatory and brotic response after immobilization [11]. This was demonstrated by the reduction in collagen content and TGF-β1 protein expression over time.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This indicates that intermuscular collagen deposition began to increase in the rst week of immobilization, but decreased after 4 weeks of immobilization. Previous studies have shown that this may be associated with gradual resolution of the in ammatory and brotic response after immobilization [11]. This was demonstrated by the reduction in collagen content and TGF-β1 protein expression over time.…”
Section: Discussionmentioning
confidence: 89%
“…Knee ROM was measured with 5.3 N-cm as the standard torque. This torque brings the knee close to its physiological limit [11] but does not damage the soft tissue [12,13]. The mobility of each left knee was measured three times by two researchers, giving six measurements.…”
Section: Measurement Of Joint Mobilitymentioning
confidence: 99%
“…For rats that underwent ACLR, we performed ACL transection and reconstruction surgery on the right knee using the methods described in previous studies. 24 , 26 Briefly, tail tendons were collected from anesthetized rats (ketamine; 80 mg/kg, xylazine; 10 mg/kg, intraperitoneally), and quadruple-bundle autografts were prepared. After opening the knee joint via a medial parapatellar approach, the ACL was exposed and transected using a surgical knife.…”
Section: Methodsmentioning
confidence: 99%
“…Once developed, the patients' quality of life is greatly affected, permanent contracture with continuous deterioration develops, and the patient becomes permanently disabled [1,3]. Among many causes of joint contracture, joint immobilization is the most common one [1][2][3][4]. In the process of joint immobilization, arthrogenic and myogenic components are involved in the occurrence and development of joint contracture [1,3].…”
Section: Introductionmentioning
confidence: 99%